Opinion of Parents Towards Online Education during the COVID-19 Pandemic - Richo, Nau; Singh, Vivek (THE PRIMARY TEACHER, 2025)
The COVID-19 disease became a serious challenge worldwide and impacted all sectors, including education. Amidst the pandemic crisis, the Government of India announced a nationwide lockdown. The education sector faced challenges in adopting new pedagogies during the lockdown. The present study captures the point of view of parents towards online education that took place during the lockdown in the Papum Pare district of Arunachal Pradesh. The investigator adopted the survey method for data collection, and data frequency count and content analysis were used for analysis. Data analysis indicated that online education was an alternative mode of education during the COVID-19 pandemic, but it had some limitations